Resonance Characteristics and Effective Parameters of New Left Hand Metamaterial - Rajni Rajni; Anupma Marwaha (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
It is essential to alter effective electromagnetic parameters of a material to enhance its response. In the present work, we propose a novel Left Hand Metamaterial (LHM) structure comprising dual turn spiral resonator (DTSR) and capacitance loaded strips (CLS). This structure is numerically explored to examine the resonance and effective material parameters i.e. permeability and permittivity. The negative refraction in the unit cell is confirmed with identification of double negative region (negative permittivity, ε and negative permeability, µ ) on placing the unit cell in a waveguide with well defined Perfect Electric Conduction/Perfect Magnetic Conduction boundary conditions.